PENGARUH INTERPERSONAL TRUST DAN SOCIAL ANXIETY TERHADAP SELF DISCLOSURE PENGGUNA SECOND ACCOUNT INSTAGRAM PADA GENERASI Z DI KOTA PADANG - Widara, Raisya Haruni; Rinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of interpersonal trust and social anxiety on self-disclosure  among Generation Zusers of  Instagram second-account in Padang City. A quantitative approach with a correlational design was applied., involving 200 Generation Z respondents aged between 18 and 25 years who actively use Instagram second accounts.. Data were gatheredusing self-disclosure , interpersonal trust, and social anxiety scales and analyzed using multiple linear regression analysis. The indicate that interpersonal trust and social anxiety jointly exert a significant influence on self-disclosure  (F = 68.581; p < 0.001), with an R Square value of 0.410, indicating that 41.0of the variation in self-disclosure  is accounted for by the two independent variables., while the remaining 59.0% is attributable to other factors beyond the research model. Partially, interpersonal trust has a positive and significant effect on self- disclosure (β = 0.512; b = 0.212; p < 0.001) with an effective contribution of 28.93%, while social anxiety also shows a significant effect on self-disclosure  (β= 0.307; b = 0.138; p < 0.001) with an effective contribution of 12.10%. These findings indicate that interpersonal trust is the dominant factor in promoting self- disclosure, while social anxiety remains influential within the context of private digital spaces such as Instagram second accounts.